2010
DOI: 10.1111/j.1600-0714.2010.00919.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the neuromotor abnormality type affect the salivary parameters in individuals with cerebral palsy?

Abstract: These findings show that individuals with spastic cerebral palsy present lower salivary flow rate, pH and buffer capacity that can increase the risk of oral disease in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 20 publications
2
28
1
10
Order By: Relevance
“…This reduction in salivary flow may be a side effect of medications, or it may indicate a possible autonomic disorder, hypohydration and/or salivary gland deficiency in individuals with spastic CP. 22 Despite these considerations, in this study, a history of xerostomia was not associated with caries. The reason for this observation could be that we did not conduct specific tests to evaluate salivary flow, as the applicability of these tests in patients with CP is limited.…”
mentioning
confidence: 64%
“…This reduction in salivary flow may be a side effect of medications, or it may indicate a possible autonomic disorder, hypohydration and/or salivary gland deficiency in individuals with spastic CP. 22 Despite these considerations, in this study, a history of xerostomia was not associated with caries. The reason for this observation could be that we did not conduct specific tests to evaluate salivary flow, as the applicability of these tests in patients with CP is limited.…”
mentioning
confidence: 64%
“…The impairment of salivary functions in CP individuals has been clearly confirmed in the literature ; however, there is a lack of information concerning soluble immune‐related biomarkers in CP. Although one report has shown that individuals with brain damage may not respond appropriately when immune activation is required , for the first time, this study shows the absolute and relative increase in the SIgA in CP.…”
Section: Discussionmentioning
confidence: 93%
“…6 Tais condições os tornam mais dependentes no momento da alimentação, determinam modificação no padrão de dieta alimentar e limitam o controle do biofilme 13 . Além disso, os pacientes com paralisia cerebral apresentam baixo fluxo e baixa capacidade tampão salivares 6,14,15 , fatores que estão relacionados com o aumento do risco à cárie.…”
Section: Discussionunclassified